Efficacy of rifaximin on circulating endotoxins and cytokines in patients with nonalcoholic fatty liver disease - Gangarapu, Venkatanarayana; Tüzün İnce, Ali; Baysal, Birol; Kayar, Yusuf; Kılıç, Ülkan; Gök, Özlem; Uysal, Ömer; Şentürk, Hakan (Lippincott Williams and Wilkins, 2015)
ObjectiveRecent studies have suggested that endotoxin-induced cytokines play an important role in nonalcoholic fatty liver disease (NAFLD). Rifaximin is a nonabsorbable antibiotic that might act on Gram-negative bacteria, thereby inhibiting endotoxin proinflammatory cytokine production in patients with NAFLD. Our aim was to investigate the efficacy of rifaximin on NAFLD.MethodsForty-two patients with biopsy-proven NAFLD [15 steatosis, 27 nonalcoholic steatohepatitis (NASH)] were included in this prospective, open-label, observational cohort study. BMI and serum aspartate aminotransferase, alanine aminotransferase (ALT), gamma glutamyl transferase, lipid profile, ferritin, C-reactive protein, glucose, insulin, homeostatic model assessment as well as endotoxin, serum Toll-like receptor 4 (TlR4), interleukin-1 (IL-1), IL-6, IL-10, IL-12, and tumor necrosis factor- (TNF-) levels were measured before and after a 28-day administration of rifaximin (1200mg/daily). Results were analyzed using nonparametric Wilcoxon signed-rank tests.ResultsA mild reduction in the mean BMI (32.36.9 vs. 31.9 +/- 6.8, P=0.02) and a significant reduction in the endotoxin (0.9 +/- 0.34 vs. 0.8 +/- 0.13, P=0.03) and IL-10 (4.08 +/- 0.9 vs. 3.73 +/- 0.7, P=0.006) levels in the NASH group were noted. A significant reduction was observed in serum aspartate aminotransferase (50.4 +/- 39 vs. 33 +/- 14, P=0.01), ALT (72 +/- 48 vs. 45.2 +/- 26.3, P=0.0001), gamma glutamyl transferase (52 +/- 33 vs. 41.2 +/- 21.1, P=0.02), LDL (137 +/- 34 vs. 127 +/- 27.5, P=0.03), and ferritin (142 +/- 214 vs. 89.3 +/- 123, P=0.0001) in the NASH group, but only in ALT (50.4 +/- 26 vs. 35.5 +/- 23.25, P=0.01), and ferritin (73.6 +/- 83 vs. 55 +/- 76, P=0.004) levels decreased significantly in the steatosis group. Treatment with rifaximin did not exert a significant effect on serum levels of TLR-4, IL-1, IL-6, IL-12, or TNF- in either group.ConclusionIn NAFLD and especially in NASH, short-term administration of rifaximin appears to be safe and effective.
WOS: 000356588500012
PubMed ID: 26043290
Keywords: Endotoxins; Gut Microbiota; Lipopolysaccharides; Nonalcoholic Fatty Liver Disease; Rifaximin